LEGAL ISSUES ASSOCIATED WITH NEPOTISM IN THE WORKPLACES IN THE SLOVAK REPUBLIC - Jana Žuľová (European Scientific Journal, ESJ, 2015)
This paper provides a new approach to the conceptualization of nepotism during the performance of the wage labour, which is, in the conditions of the Slovak Republic and in the environment of the labour market, established as an “unwritten rule”. The starting point is an understanding of nepotism as a form of preferential selection of employees, in which family members are preferred. We analyze the legal regulation of two of the most frequent forms of nepotism: i.e. 1) appointing family members to public offices (public sector) and 2) employment of family members in so-called family businesses (private sector). The differentiation of nepotism regulation in the public and private sector has been chosen as a criterion for research of legal aspects of nepotism. Legal regulation is different and understandably stricter within the public sector, but as we argue in the paper, its real effectiveness in the Slovak environment is very weak.